Perception of low social pressure and lack of capacity reduces vaccination compliance – The case of lumpy skin disease. Issue 5 (29th June 2022) - Morgenstern, Michal; Sok, Jaap; Klement, Eyal
Abstract: Successful prevention of epidemics depends on implementation of control measures, including vaccine compliance and maintenance of high vaccination coverage for long periods. However, to the best of our knowledge, a study of the temporal dynamics of compliance in voluntary vaccination campaigns and of the factors which influence them was never published. In this study, we investigated the factors influencing the dynamics of vaccination compliance against lumpy skin disease (LSD) after the occurrence of LSD epidemics in Israel in 2012–2013 and 2019. From 2016 to 2019, we followed voluntary LSD annual vaccination among a cohort of 566 farmers and used questionnaires based on the theory of planned behaviour to investigate the incentives influencing vaccine compliance among 90 farmers. The results showed a reduction in vaccination against LSD from 61% in 2016 to 27% in 2019 and a very strong association between prior vaccination and vaccination compliance. The actual vaccination by farmers who stated a positive intention to vaccinate was 4.5 times higher than farmers who did not ( p ‐value = .007). However, half of the highly intended farmers eventually did not vaccinate their herd. These farmers were significantly more concerned by manpower and vaccine price compared to their vaccinating counterparts, pointing to vaccination effort perceptions as a major factor influencing compliance. In addition, we found that farmers who answered the questionnaires before the LSD epidemic of 2019 perceived significantly less pressure to vaccinate imposed by veterinary organizations (private and governmental) than farmers answering them during or after the epidemic. We conclude that the veterinarian‐associated social pressure is a major compliance‐enhancing factor, influenced by the occurrence of an epidemic. Our findings suggest that the deterioration of vaccination compliance after an epidemic can be mitigated by maintenance of pressure to vaccinate by veterinarians. Manpower support and vaccine discounts may be advocated to promote vaccine compliance.